2009
DOI: 10.1039/b822015h
|View full text |Cite
|
Sign up to set email alerts
|

Green nanotechnology from tea: phytochemicals in tea as building blocks for production of biocompatible gold nanoparticles

Abstract: Phytochemicals occluded in tea have been extensively used as dietary supplements and as natural pharmaceuticals in the treatment of various diseases including human cancer. Results on the reduction capabilities of phytochemicals present in tea to reduce gold salts to the corresponding gold nanoparticles are presented in this paper. The phytochemicals present in tea serve the dual roles as effective reducing agents to reduce gold and also as stabilizers to provide robust coating on the gold nanoparticles in a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
255
0
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 362 publications
(261 citation statements)
references
References 106 publications
(139 reference statements)
3
255
0
3
Order By: Relevance
“…Recently, the green synthesis or fabrication of Au nanostructures have been considerably studied by using harmless alternative biocompatible molecules such as proteins, peptides, cellulose, soybeans, gellan gum, vitamin B2, starch, and D-glucose as stabilizing or reducing agents [5][6][7][8][9][10][11][12][13][14]. We also developed a facile route for the synthesis of Au nanoparticles by the use of food additives [15].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, the green synthesis or fabrication of Au nanostructures have been considerably studied by using harmless alternative biocompatible molecules such as proteins, peptides, cellulose, soybeans, gellan gum, vitamin B2, starch, and D-glucose as stabilizing or reducing agents [5][6][7][8][9][10][11][12][13][14]. We also developed a facile route for the synthesis of Au nanoparticles by the use of food additives [15].…”
Section: Introductionmentioning
confidence: 99%
“…Tea consists of two major categories of polyphenolic compounds, namely thearubigins and theaflavins. The three major constituents of theaflavins are Epigallocatechin gallate, Epigallocatechin and Epicatechin gallate [17]. Figure 1a-c depicts the chemical structures of Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, due to their cumbersome procedures such as maintaining cell cultures under specified laboratory conditions have made them less attractive, when compared to using plant products for synthesis of nanomaterials. Many plants or plant products have been employed for the synthesis of Au NPs, some of which include, Emblica officinalis, Acacia nilotica (Babool), alfalfa biomass, geranium, Azadirachta indica leaves, gum kondagogu, gram-beans and tea leaves [10][11][12][13][14][15][16][17]. Camellia sinensis commonly known as tea is a rich source of polyphenolic compounds, which exhibits a variety of health benefits such as protection against heart diseases, cancer and the paralytic actions of botulinum neurotoxins [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that consumption of cruciferous vegetables lead to a consequent decrease in the incidence of many cancers [30]. Decrease in the risk of bladder cancer is also directly related to broccoli intake [31]. The effectiveness of Se in broccoli against cancer, the inclusion of many other anticancer compounds, and the general acceptability of broccoli by the public should make this vegetable an excellent source of supplemental dietary Se.…”
Section: Uv-vis Absorbance Spectroscopy Analysismentioning
confidence: 99%